Palm kernel oil leaching - Morad, Noor Azian; Abdul Aziz, Mustafa Kamal; Sabri, Abu Safian; Ismail, Buliam (1989)
This research is in its preliminary stage in which the efficiencies of the various methods of extraction were determined. The fundamental aspects of the process of extraction was also explored in an attempt to understand it better. Improved technique of analysis was investigated. To initiate the research it is essential to understand the process and develop correlations of the findings where possible for the bench and pilot scale extractor.